Respuesta :
Answer :
(a) The rate law for the reaction is:
[tex]\text{Rate}=k[OCl^-]^1[I^-]^1[/tex]
(b) The value of rate constant is, [tex]60.4M^{-1}s^{-1}[/tex]
(c) rate of the reaction is [tex]6.52\times 10^{-5}Ms^{-1}[/tex]
Explanation :
Rate law : It is defined as the expression which expresses the rate of the reaction in terms of molar concentration of the reactants with each term raised to the power their stoichiometric coefficient of that reactant in the balanced chemical equation.
For the given chemical equation:
[tex]OCl^-+I^-\rightarrow OI^-+Cl^-[/tex]
Rate law expression for the reaction:
[tex]\text{Rate}=k[OCl^-]^a[I^-]^b[/tex]
where,
a = order with respect to [tex]OCl^-[/tex]
b = order with respect to [tex]I^-[/tex]
Expression for rate law for first observation:
[tex]1.36\times 10^{-4}=k(1.5\times 10^{-3})^a(1.5\times 10^{-3})^b[/tex] ....(1)
Expression for rate law for second observation:
[tex]2.72\times 10^{-4}=k(3.0\times 10^{-3})^a(1.5\times 10^{-3})^b[/tex] ....(2)
Expression for rate law for third observation:
[tex]2.72\times 10^{-4}=k(1.5\times 10^{-3})^a(3.0\times 10^{-3})^b[/tex] ....(3)
Dividing 1 from 2, we get:
[tex]\frac{2.72\times 10^{-4}}{1.36\times 10^{-4}}=\frac{k(3.0\times 10^{-3})^a(1.5\times 10^{-3})^b}{k(1.5\times 10^{-3})^a(1.5\times 10^{-3})^b}\\\\2=2^a\\a=1[/tex]
Dividing 1 from 3, we get:
[tex]\frac{2.72\times 10^{-4}}{1.36\times 10^{-4}}=\frac{k(1.5\times 10^{-3})^a(1.5\times 10^{-3})^b}{k(1.5\times 10^{-3})^a(3.0\times 10^{-3})^b}\\\\2=2^b\\b=1[/tex]
Thus, the rate law becomes:
[tex]\text{Rate}=k[OCl^-]^a[I^-]^b[/tex]
a = 1 and b = 1
[tex]\text{Rate}=k[OCl^-]^1[I^-]^1[/tex]
Now, calculating the value of 'k' (rate constant) by using any expression.
[tex]1.36\times 10^{-4}=k(1.5\times 10^{-3})(1.5\times 10^{-3})[/tex]
[tex]k=60.4M^{-1}s^{-1}[/tex]
Now we have to calculate the rate for a reaction when concentration of [tex]OCl^-[/tex] and [tex]I^-[/tex] is [tex]1.8\times 10^{-3}M[/tex] and [tex]6.0\times 10^{-4}M[/tex] respectively.
[tex]\text{Rate}=k[OCl^-][I^-][/tex]
[tex]\text{Rate}=(60.4M^{-1}s^{-1})\times (1.8\times 10^{-3}M)(6.0\times 10^{-4}M)[/tex]
[tex]\text{Rate}=6.52\times 10^{-5}Ms^{-1}[/tex]
Therefore, the rate of the reaction is [tex]6.52\times 10^{-5}Ms^{-1}[/tex]